Extra fluids for breastfeeding mothers for increasing milk production (Review) (2014)
Background: Breastfeeding is known to be the biological norm. Despite this, many women wean their babies because of perceived insufficient breast milk production. Mothers are sometimes advised to increase their fluid intake in the hope that this could improve breast milk production. The effect of extra fluid on human breast milk production is not well established, however. Objectives: To assess the effect of extra fluid for breastfeeding mothers on milk production/supply and infant growth. Search methods We searched the Cochrane Pregnancy and Childbirth Group’s Trials Register (27 April 2014), MEDLINE (1966 to 27 April 2014), African Journals Online (27 April 2014) and reference lists of retrieved studies. Selection criteria: Randomised controlled trials and quasi-randomised controlled trials on extra fluids for breastfeeding mothers. Data collection and analysis Two review authors independently assessed the potential studies for inclusion and assessed trial quality. Main results: Five trial reports were retrieved using the search strategies. Four trials were excluded. We did not identify any randomised controlled trials for inclusion but we included one quasi-randomised study (involving 210 women) that evaluated the effect of extra fluid for breastfeeding mothers on breastfeeding outcomes. The study was considered to be at a high risk of bias. Only one of this review’s primary outcomes was reported (breast milk production (as defined by the trialist)) but data were not in a suitable format for analysis (no standard deviations or standard errors were reported). The trialist reported that advising women to drink extra fluids did not improve breast milk production. No data were reported for the review’s other primary outcomes: satisfactory weight gain in the infant (as defined by the trialists) and duration of exclusive breastfeeding (months). Similarly, no data were reported for any of this review’s secondary outcomes: duration of any breastfeeding; mother’s satisfaction with breastfeeding; hydration in mother; dehydration in the infant; or episodes of gastrointestinal illness.